Price-Money Relationship After Inflation Targeting: Cointegration Test With Structural Breaks For Turkey and Brazil - Dumrul, Cuneyt; Dumrul, Yasemin (International Journal of Economics and Financial Issues, 2015)
The inflation targeting (IT) strategy may create structural changes in macroeconomic variables. This study analyzes the effect of the IT strategy on the price-money supply relationship in Turkey and Brazil by Kejriwal-Perron cointegration analysis with structural breaks. The analysis aims to determine whether the IT strategy leads to regime shifts in the price index-money supply relationship in Turkey and Brazil. The Kejriwal-Perron tests reveal a structural break in the price-money supply relationship as a result of the IT strategy. In both countries, the implementation of this strategy leads to a decrease in the regime coefficients for Turkey while it creates an increase for Brazil. When Turkey and Brazil are compared in terms of money-price relationship after the IT strategy, the study reveals that it has weakened more in Brazil. Keywords: Monetary Inflation; Inflation Targeting; Kejriwal-Perron Cointegration Analysis; Regime Shifts. JEL Classifications: C32; E51; E52; E58